SYNTHESIS OF 1-(2-CARBOXYPHENYL)-1'-N-METHYL OXYFERROCENYL THIOAMIDE AND BIOSTIMULATORY PROPERTIES (Scientific journal of the Fergana State University, 2023)
The article presents data on the study of o-ferrocenylbenzoic acid, a derivative of o-ferrocenylbenzoic acid with methylolthiourea, its synthesis of water-soluble potassium and sodium salts, as well as their biological activity.